Consumer Preferences for Tobacco Waste Diversification in Na Oogst Jember Cigars - Nanang Dwi Wahyono; Dewi Kurniawati; Avisenna Harkat; Mohammad Edwinsyah Yanuan Putra; Fredy Eka Ardhi Pratama; Aditya Wahyu Winadi Atmajaya (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The high demand for cigarettes yearly produces tobacco waste in the form of unused tobacco leaf stalks. Tobacco leaf stalks have high burning power and sufficient calorific value to produce heat energy, so that tobacco leaf stalks can be used as a mixture of cigarettes and as a substitute for cloves. The purpose of this study is to utilize tobacco waste, especially tobacco leaf stalks, as a mixture of cigarettes to analyze consumer diversification of tobacco waste and to improve consumer preferences for Hand-Rolled Cigarettes (SKT) with a mixture of tobacco leaf stalks—this research as conducted in March-August 2024 using a quantitative method with a non-probability sampling sample data source. The data sources for this study are secondary data and primary data. The total population of respondents is 25 people. This research is based on consumer preferences for the attributes of Taste, Flavor, strength, smoke texture, and taste. The data analysis method employed was multiple linear regression using software and the Quality Function Deployment (QFD) method. The study revealed that tobacco waste affected taste, flavor, strength, smoke texture, and aftertaste. The results of the software analysis tool showed a significant joint influence of 0.423 on each attribute of consumer preferences. The attributes that have a significant partial effect are flavor and aftertaste attributes. Consumer preference assessment using QFD analysis can affect product quality attributes after taste, which need improvement to meet consumer preferences. Fulfillment of product quality attributes after taste that needs improvement are sweet and bitter attributes at the end.